Penerapan Supervisi Klinis Untuk Meningkatkan Keterampilan Dasar Mengajar Guru di SDN 165/X Catur Rahayu pada Semester Ganjil Tahun Ajaran 2021/2022 - Siti Muslimah (Journal on Education, 2022)
This research is motivated by the basic skills of teaching teachers in elementary schools that need to be improved again. The purpose of this study was to obtain information and discuss the application of clinical supervision to improve the basic teaching skills of teachers at SDN.165/X Catur Rahayu in the odd semester of the 2021/2022 academic year. This research is a school action research (PTS) which consists of two cycles where each cycle consists of four stages, namely planning, implementation, observation, and reflection, data collection techniques using observation sheets, field notes, and documentation. Data were analyzed using percentages and data reduction. The results showed that the application of clinical supervision could improve the basic teaching skills of teachers at SDN.165/X Catur Rahayu. Using a clinical supervision approach is an approach in supervision that is considered effective for improving teacher skills in the learning process.